On the fractality of the biological tree-like structures. Issue 4 (1999) - Kalda, Jaan
Abstract : The fractal tree-like structures can be divided into three classes, according to the value of the similarity dimensionD s : D s < D, D s = D andD s > D, whereD is the topological dimension of the embedding space. It is argued that most of the physiological tree-like structures haveD s ≥ D . The notion of the self-overlapping exponent is introduced to characterise the trees withD s > D . A model of the human blood-vessel system is proposed. The model is consistent with the processes governing the growth of the blood-vessels and yieldsD s = 3.4 . The model is used to analyse the transport of passive component by blood.